"Economizing" TEPCO's Responsibility for the Fukushima Daiichi Nuclear Power Plant Accident. (2nd September 2021) - Kanamori, Eri
Abstract: The purpose of this paper is to show that the responsibility of Tokyo Electric Power Company Holdings, Inc. (TEPCO) was "economized" in the wake of the accident. It is argued that responsibility for the nuclear accident was mainly linked to economic responsibility, and that social and moral responsibility were consequently obscured by the financial accounting that followed the accident. This paper also proposes that the responsibility for the accident should not be limited to TEPCO, but that the responsibility of the nuclear industry and regulatory bodies should be more strongly emphasized in order to prevent such accidents in the future. These conclusions are consistent with some of the literature that emerged following the Fukushima accident. The theoretical framework is derived from sociological studies on quantification and accounting literature on economizing. TEPCO's accounts, the special business plans of TEPCO and the Nuclear Damage Compensation and Decommissioning Facilitation Corporation, and documentation from the Ministry of Economy, Trade and Industry are the main sources that are consulted in this paper.